ACTN3 (R577X) Genotype Is Associated With Australian Football League Players. Issue 2 (February 2022) - Jacob, Ysabel; Hart, Nicolas H.; Cochrane, Jodie L.; Spiteri, Tania; Laws, Simon M.; Jones, Anthony; Rogalski, Brent; Kenna, Jade; Anderton, Ryan S.
Abstract : Abstract: Jacob, Y, Hart, NH, Cochrane, JL, Spiteri, T, Laws, SM, Jones, A, Rogalski, B, Kenna, J, and Anderton, RS. ACTN3 (R577X) genotype is associated with Australian Football League players. J Strength Cond Res 36(2): 573–576, 2022—Genetic variants in the angiotensin-converting enzyme ( ACE ) and alpha actinin-3 ( ACTN3 ) genes have been associated with elite sport athletic performance. This study aimed to investigate the frequency of each polymorphism in a cohort of elite Australian football (AF) players. To achieve this, 47 players from an Australian Football League (AFL) club and 59 healthy age matched controls with no history of elite sporting competition were recruited for this study. Each subject provided saliva samples through buccal swab for DNA extraction and genotyping, with group comparisons made using χ 2 and odds ratio analysis. There was no significant difference in ACE I/D genotype between healthy control and elite AF players. The ACTN3 XX genotype was significantly underrepresented in AFL players (4.3%) compared with healthy controls (28.8%, p = 0.003). In addition, there was a greater representation of the R allele in elite AF players (70.2%) when compared with healthy controls (50%; χ 2 = 8.834, p = 0.002). This is the first study to investigate genetic variants in elite AF players, with results suggesting that the ACTN3 gene may play a significant role explaining aspects of athletic performance in AF.